A Phenomenology of Authenticity in Prison Life: Kierkegaard and the Paradox of Freedom - Hazel Marie Vitales; Jan Gabriel Boller; Musa, Gary; Amando Grata (Ilmu Inovasi Nusantara, 2024)
This study examines the lived experiences of selected inmates, some of whom have been released from New Bilibid Prison in Muntinlupa City, Philippines, focusing on how incarceration has transformed their lives. Faced with significant mental and emotional challenges, the inmates embraced a new life of faith amid the harsh realities of prison life. The study employs a phenomenological method to gather narratives from the inmates and analyze them thematically. The central issue this research addresses is understanding how prison experiences trigger spiritual transformation in individuals. The study's objective is to explore the spiritual changes experienced by the inmates through religious participation, using the theoretical framework of existential philosopher Søren Kierkegaard. Kierkegaard's concepts of the paradoxical nature of despair and the three stages of life—the aesthetic, the ethical, and the religious—are applied to understand the spiritual dynamics experienced by the inmates. The findings reveal that participation in religious activities can ignite profound spiritual change, even within the confines of physical and personal restrictions. The inmates' narratives highlight a journey from despair to spiritual awakening, illustrating the existential dynamics of human freedom, authenticity, and community. The study recommends providing spiritual support as an integral part of inmate rehabilitation, emphasizing how religious participation can offer inner freedom even amid physical confinement.